Small Antenna Design of Triple Band for WIFI 6E and WLAN Applications in the Narrow Border Laptop Computer - Wei-Chiang Jhang; Jwo-Shiun Sun (International Journal of Antennas and Propagation)
This paper presents the design of a small antenna for use in a wireless local area network (WLAN) and Wi-fi 6E on a narrow-border laptop. The dimensions of the antenna are 43 × 3 × 0.4 mm3, and it features a grounding system simulated by a 200 × 260 mm2 copper plate. At low-frequency bands, a couple-fed right arm can excite the fundamental at 2.45 GHz in the λ/4 resonant mode to cover the range of 2.4–2.848 GHz. At higher bands, the couple-fed left arm and direct-fed right arm can control the higher 3λ/4 mode at 5.825 GHz and 5λ/4 mode at 6.85 GHz. The direct-fed left arm excites the fundamental at 5.16 GHz in the λ/4 resonant mode and, with integration of 5.16, 5.825, and 6.85 GHz, can fully cover the range of 5.15–7.125 GHz. In far-field measurements, the peak gain and efficiency in a WLAN with Wi-Fi 6E were 0.82 and 2.58 dBi and 53% and 68% in the low and high bands, respectively. Overall, the experiments revealed that the antenna exhibits a sufficient level of performance for a narrow-border laptop.